2009
DOI: 10.1105/tpc.109.072363
|View full text |Cite
|
Sign up to set email alerts
|

Class I α-Mannosidases Are Required for N-Glycan Processing and Root Development inArabidopsis thaliana     

Abstract: In eukaryotes, class I a-mannosidases are involved in early N-glycan processing reactions and in N-glycan-dependent quality control in the endoplasmic reticulum (ER). To investigate the role of these enzymes in plants, we identified the ERtype a-mannosidase I (MNS3) and the two Golgi-a-mannosidase I proteins (MNS1 and MNS2) from Arabidopsis thaliana. All three MNS proteins were found to localize in punctate mobile structures reminiscent of Golgi bodies. Recombinant forms of the MNS proteins were able to proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
237
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(248 citation statements)
references
References 62 publications
10
237
1
Order By: Relevance
“…KOR1 has eight potential glycosylation sites in its extracellular domain, and genetic interactions of the weak KOR1 allele rsw2-1 (Lane et al, 2001) with different N-glycan-processing mutants indicate that Nglycans play a crucial role for KOR1 (Kang et al, 2008;Liebminger et al, 2009). We analyzed KOR1 expression by immunoblotting in ost3/6-1 and found that KOR1 accumulation is considerably reduced in the mutant (Fig.…”
Section: Ost3/6 Deficiency Affects the Biogenesis Of Kor1mentioning
confidence: 99%
See 1 more Smart Citation
“…KOR1 has eight potential glycosylation sites in its extracellular domain, and genetic interactions of the weak KOR1 allele rsw2-1 (Lane et al, 2001) with different N-glycan-processing mutants indicate that Nglycans play a crucial role for KOR1 (Kang et al, 2008;Liebminger et al, 2009). We analyzed KOR1 expression by immunoblotting in ost3/6-1 and found that KOR1 accumulation is considerably reduced in the mutant (Fig.…”
Section: Ost3/6 Deficiency Affects the Biogenesis Of Kor1mentioning
confidence: 99%
“…The mutants alg10-1, alg10-1 gntI, alg10 cgl1 (Farid et al, 2011), gntI (Kang et al, 2008), stt3a-2 (Koiwa et al, 2003), cgl1 (von Schaewen et al, 1993, efr-1 (Zipfel et al, 2006), fls2c efr-1 ), rsw2-1 (Lane et al, 2001), bri1-9, and bri1-5 (Noguchi et al, 1999) are all available from previous studies (Zipfel et al, 2006;Liebminger et al, 2009;Farid et al, 2011;Hüttner et al, 2012). Tunicamycin, ABA, and other chemicals for seedling germination and growth assays were purchased from Sigma-Aldrich.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…In mammals, for instance, N-linked glycosylation is involved in cell adhesion, molecular trafficking and clearance, receptor activation, signal transduction, and endocytosis and is important for human health and disease (Ohtsubo and Marth, 2006). In higher plants, enzymes involved in protein N-glycosylation and glycoproteins that are N-glycosylated have been widely identified and found to play vital roles in diverse aspects of development and physiology, including salt tolerance and plant immunity (Lerouge et al, 1998;Kang et al, 2008;Qin et al, 2008;Liebminger et al, 2009;Saijo et al, 2009;Häweker et al, 2010;Liu and Howell, 2010;Ruiz-May et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of 1-deoxymannojirimycin, another specific mannosidase inhibitor from the class of 1-deoxyazasugars, resulted in an important increase of the half maximal inhibitory concentrations compared to kifunensine (IC 50 of 30-40 µM) 89 . In another study, the inhibition coefficient of jack bean α-mannosidase by 1-deoxymannojirimycin was even higher: IC 50 = 840 µM 93 .…”
Section: High Mannose Speciesmentioning
confidence: 99%
“…It was also observed that the acidic form was sensitive to swainsonine, a potent inhibitor of the class I enzyme 103 . The inhibitory effect of swainsonine on the class II enzyme had been described previously 89 . The bicyclic derivative of 1-deoxymannojirimycin, castanospermine, an indolizine alkaloid isolated from the seeds of the Australian chest nut tree Castanosperum australe 104 , inhibits the ER glucosidase enzymes, and as a result, further glycan processing 105 .…”
Section: High Mannose Speciesmentioning
confidence: 99%